Diagnostic tests of cross section independence for nonlinear panel data models - Cheng Hsiao; Mohammad Hashem Pesaran; Andreas Pick (Center for Economic Studies and ifo Institute (CESifo), 2007)
In this paper we discuss tests for residual cross section dependence in nonlinear panel data models. The tests are based on average pair-wise residual correlation coefficients. In nonlinear models, the definition of the residual is ambiguous and we consider two approaches: deviations of the observed dependent variable from its expected value and generalized residuals. We show the asymptotic consistency of the cross section dependence (CD) test of Pesaran (2004). In Monte Carlo experiments it emerges that the CD test has the correct size for any combination of N and T whereas the LM test relies on T large relative to N. We then analyze the roll-call votes of the 104th U.S. Congress and find considerable dependence between the votes of the members of Congress.
Keywords: C12; C33; C35; 330; Statistischer Test; Panel; Nichtlineares Verfahren; Theorie